Design of Android-Based Financial Recording Applications in the Shoes Business - Badruz Alkatiri; Andi Purnomo (Universitas Amikom Purwokerto, 2022)
Surf Skate Shop is a shop that sells various kinds of shoes in Purwokerto. In managing their finances, shop owners still use bookkeeping that is written manually on books. Records written in books may experience errors such as lost documents, difficulty in finding documents and errors in calculations. Therefore this research is directed to be able to assist shop owners in managing their finances. In making this application the researcher uses a type of qualitative data collection method, namely observation, interviews, literature study, and documentation. While in the development of the system using extreme programming method. The results of this study are in the form of an Android-based financial records application that can record sales data, record expense data, record item data, store data so that it is not easily lost and damaged, calculate the number of items sold, calculate total sales, calculate total expenses, calculate total profits, calculating the operational amount, calculating the total net profit and calculating the total that must be deposited to the supplier, searching for data by date, and displaying what items were sold to the supplier. Based on testing with the user acceptance testing method with the results of the respondents being 95% so that it is included in the category of approving the system to be an application that can help manage financial records.